2018
DOI: 10.1002/ange.201805738
|View full text |Cite
|
Sign up to set email alerts
|

The β‐Agostic Structure in (C5Me5)2Sc(CH2CH3): Solid‐State NMR Studies of (C5Me5)2Sc−R (R=Me, Ph, Et)

Abstract: Multinuclear solid-state NMR studies of Cp* 2 ScÀR (Cp* = pentamethylcyclopentadienyl;R = Me,P h, Et) and DFT calculations show that the ScÀEt complex contains a b-CH agostic interaction. The static central transition 45 Sc NMR spectra show that the quadrupolar coupling constants (C q ) follow the trend of Ph % Me > Et, indicating that the Sc À R bond is different in Cp* 2 ScÀEt compared to the methyl and phenyl complexes.Analysis of the chemical shift tensor (CST) shows that the deshielding experienced by Cb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The residue from toluene solutions of 4 contained signals consistent with the formation of Cp* 2 Sc(CH 2 C 6 H 5 ) as well signals that most likely correspond to a mixture of the previously reported ortho- , meta- , and para -tolyl Cp* 2 Sc(C 6 H 4 CH 3 ) complexes . The crude material obtained from the reduction in Et 2 O displayed a signal corresponding to unreacted Cp* 2 ScI along with signals, which suggested the formation of Cp* 2 Sc(OCH 2 CH 3 ) and the previously reported Cp* 2 Sc(CH 2 CH 3 ) . These three signals appeared in an approximate 1:1:0.8 ratio.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…The residue from toluene solutions of 4 contained signals consistent with the formation of Cp* 2 Sc(CH 2 C 6 H 5 ) as well signals that most likely correspond to a mixture of the previously reported ortho- , meta- , and para -tolyl Cp* 2 Sc(C 6 H 4 CH 3 ) complexes . The crude material obtained from the reduction in Et 2 O displayed a signal corresponding to unreacted Cp* 2 ScI along with signals, which suggested the formation of Cp* 2 Sc(OCH 2 CH 3 ) and the previously reported Cp* 2 Sc(CH 2 CH 3 ) . These three signals appeared in an approximate 1:1:0.8 ratio.…”
Section: Resultssupporting
confidence: 53%
“…The mixture immediately became dark red in color and was allowed to stand at this temperature for 18 h. After the mixture was allowed to warm to ambient temperature and stirred for 1 h, the solution was decanted from the black solids, presumably graphite, at the bottom of the vial, and the solvent was removed from this solution under reduced pressure to give a yellow residue. This crude residue was then dissolved in C 6 D 6 for study by 1 H NMR spectroscopy, which showed resonances consistent with the presence of Cp* 2 ScI, Cp* 2 ScCH 2 CH 3 , and a third complex that we have tentatively assigned as Cp* 2 ScOCH 2 CH 3 . 1 H NMR (500 MHz, C 6 D 6 ): δ = 4.49 (q, 2H, OC H 2 CH 3 (Cp* 2 ScOEt), J HH = 6.9 Hz), 1.93 (s, 30H, CH 3 ( Cp* 2 ScOCH 2 CH 3 )), 1.91 (s, 30H, CH 3 ( Cp* 2 ScI)), 1.86 (s, 30H, CH 3 ( Cp* 2 ScCH 2 CH 3 ), 1.33 (t, 3H, CH 3 (Cp* 2 ScOCH 2 C H 3 ), J HH = 6.9 Hz), 0.99 (q, 2H, CH 2 (Cp* 2 ScC H 2 CH 3 ), J HH = 8.2 Hz), 0.17 (t, 3H, CH 3 (Cp* 2 ScCH 2 C H 3 ), J HH = 8.2 Hz).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rh(CO) 2 Cp*, the only compound herein with an η 5 -coordinated cyclopentadienyl ring, has a δ iso = −1150 ppm, the lowest in this set, which is indicative of an extremely shielded 103 Rh nucleus as is typical for δ iso values of metal nuclides in metallocenes. 132–135 The relationships between the 103 Rh chemical shift tensor parameters and structure and bonding in this set of Rh complexes is further explored with DFT calculations (see Sections 3.2 and 3.3).…”
Section: Resultsmentioning
confidence: 99%